2000
DOI: 10.1095/biolreprod63.2.635
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone-Stimulated Sperm Binding to the Human Zona Is Mediated by a Calcium Influx1

Abstract: The mechanism by which GnRH increases sperm-zona pellucida binding in humans was investigated in this study. We tested whether GnRH increases sperm-zona binding in Ca(2+)-free medium and in the presence of Ca(2+) channel antagonists. We also examined the GnRH effect on the intracellular free Ca(2+) concentration ([Ca(2+)](i)). Sperm treatment with GnRH increased sperm-zona binding 300% but only when Ca(2+) was present in the medium. In Ca(2+)-free medium or in the presence of 400 nM nifedipine, 80 microM dilti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…Our finding that Ln induces the AR and Ca 2þ influx supports the hypothesis that a6b1 integrin has an outside-in signaling function in the sperm. Furthermore, the existence of L-type calcium channels has already been reported in human sperm [80][81][82]. We also found that epoxomicin, an inhibitor of proteasome activity, decreased the plateau phase of the Lninduced calcium entry into the sperm cells, while the transient initial peak was unaffected.…”
Section: Discussionsupporting
confidence: 79%
“…Our finding that Ln induces the AR and Ca 2þ influx supports the hypothesis that a6b1 integrin has an outside-in signaling function in the sperm. Furthermore, the existence of L-type calcium channels has already been reported in human sperm [80][81][82]. We also found that epoxomicin, an inhibitor of proteasome activity, decreased the plateau phase of the Lninduced calcium entry into the sperm cells, while the transient initial peak was unaffected.…”
Section: Discussionsupporting
confidence: 79%
“…A recent report demonstrated that when glycodelin binds to its receptor on T cells, CD45, it can act as a calcium-dependent lectin to bind other T cell surface glycoproteins to mediate its immunoregulatory activities (70). Gonadotropin-releasing hormone increases spermatozoa-zona binding via an elevation of intracellular calcium through T-type voltage-operated calcium channels (71). It is also possible that glycodelin-C induces signal transduction leading to the formation of more functional zona pellucida receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, GnRH antagonists inhibit, in vivo and in vitro , fertilization in rodents (14) whereas sperm binding to the human zona pellucida and calcium influx in response to GnRH and progesterone have been reported (13), providing evidence of functional role of GnRH-Rs in human SPZ.…”
Section: Gnrh a Historical Modulator Of Testis Physiologymentioning
confidence: 99%